SPR biosensor based on immobilized E.coli cells with autodisplayed Z-domains - Lee, Eun-Hang; Yoo, Gu; Jose, Joachim; Kang, Min-Jung; Song, Seung-Min; Pyun, Jae-Chul (KOREAN BIOCHIP SOCIETY-KBCS, 2012)
The Z-domains of protein A was expressed as a fusion protein at the outer membrane of E.coli by using the autodisplay technology. Because of the specific affinity towards the Fc region of immunoglobulins (IgG's), the Z-domains have been used for the orientation control of antibodies in order to improve the sensitivity of immunoassays. In this work, the E.coli with autodispalyed Z-domains was immobilized to the SPR biosensor by the charge interaction. The surface modification was carried out by covalent layering of the poly-L-lysine with amino groups to the parylene-H film with formyl groups. And then, the negatively charged E.coli cells were immobilized by charge interaction with the positivley charged of poly-L-lysine. The effectiveness of this layer for the immobilization of E.coli was estimated by counting the number of E.coli cells in comparison with the bare gold surface and the poly-L-lysine coated gold surface. For the test of feasibility of the immobilized E.coli cells to SPR biosensor, the stability of immobilized E.coli cells was estimated by treatment of salt solutions at the known concentrations to the immobilized E.coli cells which were bound through the charge interaction. From this test, the E.coli cells immobilized to the parylene-H film with poly-L-lysine coating were determined to be stable at the salt concentration of human serum. Then, the applicability of the immobilized E.coli cells with autodisplayed Z-domains was demonstrated by detection of C-reactive protein (CRP). The effect of orientation control with autodisplayed Z-domains was estimated by comparing the sensivities by immobilization through the physical adsorption and charge interaction to poly-L-lysine coated layer.